Nowe złożenia w rosyjskich elektronicznych środkach przekazu - Рацибурская, Лариса (Studia Rossica Posnaniensia, 2016)
The article considers the structure and functions of compound innovations in online Russian mass media. These innovations are composed by the usual means of pure composition and root affixation. Contaminated innovations, which are non-standard in structure, are also analyzed. The factors contributing to the expressiveness of innovations are singled out: irregularity of derivational structure, non-usual combinations of constituent parts of innovations, play upon precedent phenomena.